Perancangan UI/UX Aplikasi Emergency Untuk Kekerasan Seksual Dengan Metode Design Thinking - Arlisya Purbasari; Didi Juardi (Jurnal Ilmiah Wahana Pendidikan, 2023)
The purpose of this research is to design a product or application that can help the community, especially victims of sexual violence or harassment that occurs in Indonesia, whether male or female, because all deserve a sense of security and protection, through the SaveWo application, researchers conduct research that can be a solution to the problem of sexual violence, After testing with the SUS technique, a score of 78 was obtained which is included in the acceptable category or can be accepted with grade B which indicates the appearance and flow of the application is easy to understand, but some users experience many errors or missclicks which indicate that it needs to be reviewed so that users no longer experience missclicks, but even so, based on the results of calculations and feedback submitted by users for prototypes and features designed in accordance with user needs.